Differences in the attitudes to sport psychology consulting between individual and team sport athletes - Dáire Rooney; Robin C. Jackson; Neil Heron (BMC, 2021)
Abstract Background The purpose of the present study was to investigate how an athlete's participation in either an individual or team sport is related to their attitude toward sport psychology consulting and their willingness to consult a sport psychology practitioner. Method The Sport Psychology Attitudes-Revised form (SPA-R) (Martin, et al., Sport Psychol 16:272-90, 2020) was completed by 120 athletes from individual and team sports. A 2 (Type of sport: individual and team) × 2 (Gender) multivariate analysis of variance (MANOVA) was conducted with attitudes towards sport psychology as dependent variables. To identify attitudes that accentuated the differences related to type of sport, follow-up univariate analyses were performed. Results Results revealed that overall athletes involved in individual sports reported more positive attitudes towards sport psychology consulting than athletes involved in team sports. In particular, the athletes involved in individual sports were more likely to have greater confidence in sport psychology consulting. The findings also show that gender may mediate this association, indicated by a nearly significant two-way interaction effect for gender and type of sport (individual versus team) regarding confidence in sport psychology. The source of this marginal result was a larger effect of sport type for females than for males. Conclusions The findings of this study imply that athletes involved in individual sports are more likely to have positive attitudes towards sport psychology compared to athletes competing in team-based sports, with females more likely to view sport psychology positively than compared to their male counterparts. The results may go some way to assist sport psychologists to understand and address athletes' concerns and to improve receptivity to sport psychology services.